Making the Second Ghetto: Race and Housing in Chicago, 1940-1960 - Goheen, Peter G. (Labour / Le Travail, 1985)
This article reviews the book, "Making the Second Ghetto: Race and Housing in Chicago, 1940-1960," by Arnold R. Hirsch.
Keywords: HIRSCH; Arnold R.; Housing; MAKING the Second Ghetto: Race & Housing in Chicago 1940-1960 (Book); Nonfiction; REVIEWS; books